It is (1, 1).
Since this question is in the calculus section, I'm assuming you know how to take the derivative. We know that y = -2x2 + 2x + 3 is a parabola, so it has one vertex, which is a minimum. We can use the first derivative test to find this extreme point.First, take the derivative:y' = -4x + 2Next, set y' equal to zero:0 = -4x + 2Then solve for x:4x = 2x = 2This is the x-coordinate of the vertex. To find the y-coordinate, plug x = 2 back into the original equation:y = -2x2 + 2x + 3y = -8 + 4 + 3y = -1So the vertex is at (2, -1).
f(x) = -2x2 + 2x + 8 ∴ f'(x) = -4x + 2 Let f'(x) = 0: 0 = -4x + 2 ∴ 4x = 2 ∴ x = 0.5 Now find the corresponding value: f(0.5) = -2(0.5)2 + 2(0.5) + 8 = -0.5 + 1 + 8 = 8.5 So the vertex of this parabola occurs at the point (0.5, 8.5)
y = 2x2 + 4x - 3 This equation describes a parabola. Because it's first term is positive, we know that it goes infinitely upward, and has a minimum that occurs at it's vertex. You can find it's vertex by taking it's derivative and solving for zero: y' = 4x + 4 0 = 4x + 4 0 = x + 1 x = -1 y = (-1)2 + 4(-1) - 3 y = 1 - 4 - 3 y = -6 So the vertex is at (-1, -6), which means that y ≥ -6
4x4 + 1 = (2x2 - 2x + 1)(2x2 + 2x + 1)
It is (1, 1).
Since this question is in the calculus section, I'm assuming you know how to take the derivative. We know that y = -2x2 + 2x + 3 is a parabola, so it has one vertex, which is a minimum. We can use the first derivative test to find this extreme point.First, take the derivative:y' = -4x + 2Next, set y' equal to zero:0 = -4x + 2Then solve for x:4x = 2x = 2This is the x-coordinate of the vertex. To find the y-coordinate, plug x = 2 back into the original equation:y = -2x2 + 2x + 3y = -8 + 4 + 3y = -1So the vertex is at (2, -1).
Assuming the missing symbol there is an equals sign, then we have: y - 2x2 - 4x = 4 We can find it's vertex very easily by solving for y, and finding where it's derivative equals zero: y = 2x2 + 4x + 4 y' = 4x + 4 0 = 4x + 4 x = -1 So the vertex occurs Where x = -1. Now we can plug that back into the original equation to find y: y = 2x2 + 4x + 4 y = 2 - 4 + 4 y = 2 So the vertex is at the point (-1, 2)
f(x) = -2x2 + 2x + 8 ∴ f'(x) = -4x + 2 Let f'(x) = 0: 0 = -4x + 2 ∴ 4x = 2 ∴ x = 0.5 Now find the corresponding value: f(0.5) = -2(0.5)2 + 2(0.5) + 8 = -0.5 + 1 + 8 = 8.5 So the vertex of this parabola occurs at the point (0.5, 8.5)
2x2 + 3x + 1 = (x + 1)(2x + 1)
y = 2x2 + 4x - 3 This equation describes a parabola. Because it's first term is positive, we know that it goes infinitely upward, and has a minimum that occurs at it's vertex. You can find it's vertex by taking it's derivative and solving for zero: y' = 4x + 4 0 = 4x + 4 0 = x + 1 x = -1 y = (-1)2 + 4(-1) - 3 y = 1 - 4 - 3 y = -6 So the vertex is at (-1, -6), which means that y ≥ -6
4x4 + 1 = (2x2 - 2x + 1)(2x2 + 2x + 1)
The vertex is at (-1,0).
2x2 + 5x - 3 (2x - 1)(x + 3)
2x2+5x+3 = (2x+3)(x+1) when factored
2x2 - 9x + 4 = (2x - 1)(x - 4)
If: 2x2-3x+1 = 0 Then: x = 1 or x = 1/2